Spectrofluorimetric Determination of Atenolol and Carvedilol in Pharmaceutical Preparations after Optimization of Parameters using Response Surface Methodology - Ahad Bavili-Tabrizi; Faezeh Yousefzadeh (Tabriz University of Medical Sciences, 2019)
Background: The present work is aimed to study the effect of different parameters on the fluorescence intensity of atenolol (ATE) and carvedilol (CAR) and optimization by response surface methodology (RSM) to provide a simple analytical method for their quantification in pharmaceutical formulations. Methods: Various parameters affecting the fluorescence intensity, i.e., sodium dodecyl sulfate (SDS) concentration, pH, volume fraction of solvents were optimized using RSM. Then, the optimized parameters were applied to the validation of a method for fluorimetric determination of β-blockers in their pharmaceutical preparations. Results: It is obtained that under the optimum conditions for determination of ATE, the method provided a linear range between 130 to 750 ng/mL with a coefficient of correlation (r) of 0.9996. Also, the limit of detection and limit of quantification (LOD and LOQ) were 40 ng/mL and 130 ng/mL, respectively. Moreover, it is observed that, the linearity of method for determination of CAR was between 0.37 to 4.0 ng/mL and LOD and LOQ of method were 0.11 ng/mL and 0.37 ng/mL, respectively. Conclusion: An accurate, sensitive and reliable spectrofluorimetric method was developed anf successfully used to determine the (ATE) and carvedilol (CAR) in their pharmaceutical preparations.